PREVALENCE AND IMPACT OF GESTATIONAL HYPOTHYROIDISM ON MATERNAL AND FETAL OUTCOMES: AN OVERVIEW (Vietnam Journal of Community Medicine, 2026)
Objectives: This narrative review aimed to evaluate the prevalence, clinical characteristics, and the impact of hypothyroidism during pregnancy on maternal and fetal outcomes.Method: A narrative review.Results: Evidence from previous studies indicates that the prevalence of hypothyroidism in pregnancy ranges from 10.2-24.7%, with subclinical hypothyroidism being more predominant (1.6-9.0%). The disease often presents insidiously with nonspecific symptoms such as fatigue (62%), constipation (27%), and cold intolerance. Maternal hypothyroidism is significantly associated with increased risks of adverse outcomes, including gestational hypertension (OR = 2.3-14.1), preterm birth (OR = 2.39-4.16), and higher rates of cesarean section (OR = 1.75-4.47). Regarding fetal outcomes, the risk of low birth weight is markedly elevated (OR up to 6.3), the incidence of low APGAR scores is increased by 3.45-3.64 times, and the prevalence of congenital anomalies is 2-3 times higher compared with euthyroid pregnancies.Conclusion: Hypothyroidism during pregnancy is a common endocrine disorder associated with substantial adverse obstetric and neonatal consequences. Early screening of serum TSH and FT4 levels in the first trimester and timely intervention with Levothyroxine are crucial in reducing these risks to levels comparable to those of the general population.
Keywords: Hypothyroidism in pregnancy, maternal outcomes, fetal outcomes, subclinical hypothyroidism, pregnancy complications.